ANALISIS MANAJEMEN RISIKO SISTEM INFORMASI BERBASIS ISO 31000:2018 PADA PERUSAHAAN LOGISTIK PENGIRIMAN BARANG - Marchelino Nathanael; Yessica Nataliani (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
In an era of rapid technological development, it is important to recognize the various threats and risks that may arise along with these developments. These threats and risks can disrupt operational activities, including system usage, and even reduce system performance. PT. Merdeka Panji Mulia, a company engaged in logistics and delivery services, uses an online cashier application to support its business processes. The absence of risk management analysis in this application has led to insufficient data monitoring and the emergence of various other issues. This study aims to apply the ISO 31000:2018 framework to analyze risk management in the online cashier application. The analysis was carried out through four stages: risk identification, risk analysis, risk evaluation, and risk treatment. The results of this study identified 21 potential risks, which were classified into three categories: 3 low risks, 15 medium risks, and 3 high risks. These findings reinforce the applicability of ISO 31000:2018 in managing information system risks within the logistics sector.